Coverage Analysis of Indonesia Sustainability Assessment Tools: Similarity in Dimension and Assessment Results - Nurcahyo, Rahmat; Tattya Lokhita A.K, Komang; Sihono Gabriel, Djoko (International Journal of Engineering & Technology, 2018)
The number of sustainability assessment tools in Indonesia is growing rapidly, concerns are raised on whether the assessment results of different tools present similar and valid conclusion about the sustainability performance in manufacturing industry. In this paper, we analyze dimensions of sustainability assessment tools and compare the structures of sustainability tools in Indonesia. Using a coverage analysis to demonstrate the similarity and differences between two sustainability assessments in Indonesia (PROPER and Industri Hijau) we then compare the results of both and analyze it. This study shows that two sustainability assessment tools in Indonesia which are PROPER and Industri Hijau have high variations in their structures, indicators, criteria, and sub-themes despite their similar dimension and purpose.  Consequently,  these sustainability assessment  tools  show  differences  in  assessment results  and  conclusions  on  the  sustainability  performance  of firms. Future research may propose a new integrated sustainability assessment tool so there will be only one sustainability assessment tool in Indonesia.